Grout diffusion in silty fine sand stratum with high groundwater level for tunnel construction. (November 2019) - Liu, Xiaoli; Wang, Fang; Huang, Jin; Wang, Sijing; Zhang, Zhizeng; Nawnit, Kumar
Highlights: A theoretical analysis of the grouting process is presented. Numerical modeling of grout diffusion based on the discrete element method is performed. The analysis results are in good agreement with the values obtained in an engineering case study. Abstract: Silty fine sand stratum with a high water groundwater level is a common soil type with poor strength. During tunnel construction and foundation pit excavation, geologic hazards such as water leakage and ground subsidence are very likely if safety preparations are lacking. In this study, we conducted a theoretical analysis of the grouting process in silty fine stratum using a sleeve valve tube; the diffusion behavior of the grout with Bingham fluid characteristics was determined and simulated for different levels of pressure using the discrete element method. Theoretical analysis and numerical calculations were performed to determine the relationships between the grouting pressure, the diffusion radius, and the initial fracture pressure. A good agreement is obtained between the simulation and measured results, demonstrating the feasibility of the proposed theoretical model. The method is used in an actual grouting engineering project and good results are obtained.